A review of expert group-based science advisory processes in Canada - Cody J. Dey; Cory A. Toth; Shabana Ebadi; Rachel Vallender (FACETS)
Some of the most authoritative science advice comes from groups of experts operating under systematic advisory methods. In this paper, we compiled publicly available information on 676 science advisory processes conducted over a 29-year period by five Canadian science advisory institutions (i.e., the Canadian Science Advisory Secretariat, the National Advisory Council on Immunization, the Canadian Council of Academics, the Royal Society of Canada, and the Committee on the Status of Endangered Wildlife in Canada) and used these data to explore how these institutions operate. Despite common objectives, we found considerable variation among institutions, including in the number of experts involved in developing and reviewing advice, the length of resulting science advice documents, and the time required for individual science advisory processes to be completed. In general, the institutions have become more transparent over time, driven primarily by disclosing more information on the experts involved. Additionally, we found that science advice reports have become lengthier, and the delivery of science advice now takes considerably more time for most institutions. We discuss these findings in the context of recent criticisms of expert group-based science advisory processes and suggest there may be trade-offs associated with emphasizing different science advice principles.